Análisis de Eficiencia del Modelo de Valoración Binominal para los Bonos Globales Ecuatorianos y su Aplicación - Moreno, Juan Pablo (2006)
It has been used the model of binomial tree “Black-Derman-Toy” for a process of interest rates with the purpose of making a conceptual retrospective ex-post valuation of the Ecuadorian Global bonds, to compare them with the prices that were observed on the market. The analysis demonstrates that the model of valuation 1s efficient, since that statistically there is no difference of value between the options of implicit purchase on the market and the hypothetical prices originated in the model. Consequently, the model can be used for the design of any strategy of debt handling. In several occasions, the option of purchase included in the Global bond 2012 expired “in-the-money” and the issuer did not exercise the right, apparently for the inability to access to liquid funds for the effect, of opportune form. Under the current circumstances, for the Ecuadorian government it is optimal to repurchase the Global bonds and to refinance them. Assuming that the prices of market of January 13 of 2006 maintained, Ecuador would gain approximately USD 95 millions 1f 1t refinances the USD 1,250 million corresponding to the entire emitted amount of the Global bonds 2012.